2001
DOI: 10.1109/22.954787
|View full text |Cite
|
Sign up to set email alerts
|

Design of compact multilevel folded-line bandpass filters

Abstract: A simple design methodology for compact multilevel multiconductor folded-line bandpass filters is presented in this paper. Several new compact folded-line filter topologies in single, as well as multilevel environments are proposed. Simple closed-form design equations are presented for the extraction of an equivalent coupled transmission line representing the folded-line filter section. The folded-line filter designs are validated by full-wave electromagnetic simulation, as well as by measurement for a four-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It has relatively large size and difficulty of tuning since air core inductors are assembled on a board and controlled manually. To address these obstacles, tremendous efforts have been performed by utilizing new types of resonators, coupling structures [2,3], coupling methods [4], geometry configurations [5], and multi-level folded-line structures [6]. However, these filters are still too large to apply for compact TV tuner modules and systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has relatively large size and difficulty of tuning since air core inductors are assembled on a board and controlled manually. To address these obstacles, tremendous efforts have been performed by utilizing new types of resonators, coupling structures [2,3], coupling methods [4], geometry configurations [5], and multi-level folded-line structures [6]. However, these filters are still too large to apply for compact TV tuner modules and systems.…”
Section: Introductionmentioning
confidence: 99%
“…Another technique was presented by Eleftheriades in 2002 who introduced the concept of fabricating metamaterial using lumped elements [5]. In this article, the rat-race coupler and metamaterial structure has been used to obtain compact size [6][7][8][9]. For compact requirements, it is very interesting to design a wideband transmission line correlator for wideband communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among passive components, bandpass filters are extensively used for a variety of applications in communication systems. Several new configurations of bandpass filters have been reported in multilayered configuration [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…While LTCC filter can reduce lateral size due to relatively high dielectric constant, it may not represent the most economical solution. With an increased interest in embedded passive circuits in RF module, Raghu et al reported design methodology of compact multilevel folded-line bandpass filter [13], [14]. This paper describes a general design methodology for embedded passive components with emphasis on bandpass filter.…”
Section: Introductionmentioning
confidence: 99%